Pengaruh Brand Trust, Word of Mouth dan Sales Promotion terhadap Keputusan Pembelian Air Mineral Pristine di Kota Semarang - Vinka Alifah Ardiati; Imam Nuryanto (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to determine the influence of brand trust, word of mouth and sales promotion on purchasing decisions of Pristine mineral water in Semarang City. This research uses quantitative methods. The population of this research is the people of Semarang City who have purchased Pristine mineral water with a sample of 136 respondents. The sampling technique uses a purposive sampling method. Collection and research techniques were carried out through questionnaires and processed using SPSS 24. The results of this research show that brand trust has a positive and significant effect on purchasing decisions, word of mouth has a positive and significant effect on purchasing decisions, and sales promotion has a positive and significant effect on purchasing decisions.